The Presentation, Predisposing Factors and Outcome of Erb’s Palsy in Duhok City - Saad Mahmood Zebary; Khalid Nawaf Abdulrrahman (Advanced Medical Journal)
Background and objectives:Neonatal brachial plexus palsy is a common birth injury. Although spontaneous recov- ery is expected to occur in most of affected newborns, some might be severely handicapped. The objectives of this research were to study the predisposing factors and injury outcome of Erbs’ palsy in neonates.